Macrophytes assemblages in mountain lakes of Huerquehue National Park (39ºS, Araucanía Region, Chile) - Enrique Hauenstein (Latin American Journal of Aquatic Research, 2011)
The lakes studied (Tinquilco, Verde, Toro, Chico) are located in the Huerquehue National Park (39°08'S, 71°40'W), Chile. An inventory of the aquatic and riparian species was performed between December 2005 and March 2006. A null model analysis was done to determine the existence of regulatory factors of species associations, and the Jaccard index was applied to determine floristic similarities. Seventy-five species were identified. The greatest number (54) and highest percentage of introduced species (37%) occurred at Tinquilco Lake, placing it in the category of "high human disturbance". Verde Lake, on the other hand, presented the lowest number of species (21), and the percentage of introduced species did not exceed 20% in the other three lakes, which are considered to have "low human disturbance". The analysis of the null model revealed the presence of regulatory factors in one of the three simulations. However, in the other two simulations, the species associations appeared to be random, presumably because many species were repeated at the study sites. According to the Jaccard index, Tinquilco Lake is noticeably different from the other lakes, probably due to its transition from oligotrophy to mesotrophy.